Risk factors associated with headache prevalence among adolescents - Filho, Claudionor Antônio dos Santos; Ferreira , Athyrson de Castro; Barberino , Ana Flávia de Sousa; Marçal dos Anjos, Maíra; Santos, Paula Katherine Marques dos; Santos, Marcus Vinicius Matos dos; Barberino , Ana Paula de Sousa; Ferreira , Gleiciele de Castro (Headache Medicine, 2024)
Background: Headache prevalence among adolescents has raised growing concerns due to its association with various risk factors in their lifestyle habits. Objective: This literature review aims to identify and analyze the main determinants related to headache prevalence among adolescents. Methods: This study consists of a systematic review of literature published in the last ten years in the Virtual Health Library (BVS) and PubMed, using the descriptors "headache," "adolescent," and "risk factors." The inclusion criteria were articles that address risk factors for headache in adolescents, published in Portuguese or English. Results: A higher prevalence of headache was observed in older adolescents (16-19 years) compared to younger adolescents (12-15 years). This difference may be related to biopsychosocial factors in younger adolescents, such as stress and/or divorce in the family environment. Among headache types, migraine and tension headaches were the most frequent. Tension headaches were more prevalent in females, with women reporting more frequent headache complaints than men. This difference may be associated with hormonal factors. The study also found a significant relationship between excessive technology use and headache occurrence, especially migraine-type headaches. This association can be explained by inadequate posture habits, visual fatigue, and auditory symptoms during the use of electronic devices. Conclusion: This study highlighted a higher prevalence of headache in older adolescents and a lower prevalence among younger ones, possibly due to family stress. Migraine and tension headaches were more common in this group, with tension headaches predominant among girls. Excessive use of digital technologies was associated with headache, especially migraine-type headaches, due to inadequate postures, visual fatigue, and auditory symptoms.